2001
DOI: 10.1128/jcm.39.8.3002-3005.2001
|View full text |Cite
|
Sign up to set email alerts
|

Automated Ribotyping Using Different Enzymes To Improve Discrimination ofListeria monocytogenesIsolates, with a Particular Focus on Serotype 4b Strains

Abstract: To develop improved automated subtyping approaches for Listeria monocytogenes, we characterized the discriminatory power of different restriction enzymes for ribotyping. When 15 different restriction enzymes were used for automated ribotyping of 16 selected L. monocytogenes isolates, the restriction enzymes EcoRI, PvuII, and XhoI showed high discriminatory ability (Simpson's index of discrimination > 0.900) and produced complete and reproducible restriction cut patterns. These three enzymes were thus evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 34 publications
3
28
1
1
Order By: Relevance
“…Early multilocus enzyme electrophoresis (MEE)-based subtyping (3) and restriction enzyme analysis (57) showed that strains from many different outbreaks were closely related even though those outbreaks were geographically and temporally distinct. These findings were also supported by data generated using ribotyping (12), virulence gene polymorphism analysis (59), and pulsed-field gel electrophoresis (PFGE) (4,5,28,31). Kathariou (30,31) subsequently compared those studies and defined four epidemic clones of L. monocytogenes (epidemic clone I [ECI], ECIa, ECII, and ECIII).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Early multilocus enzyme electrophoresis (MEE)-based subtyping (3) and restriction enzyme analysis (57) showed that strains from many different outbreaks were closely related even though those outbreaks were geographically and temporally distinct. These findings were also supported by data generated using ribotyping (12), virulence gene polymorphism analysis (59), and pulsed-field gel electrophoresis (PFGE) (4,5,28,31). Kathariou (30,31) subsequently compared those studies and defined four epidemic clones of L. monocytogenes (epidemic clone I [ECI], ECIa, ECII, and ECIII).…”
mentioning
confidence: 60%
“…1). The isolates from the coleslaw outbreak (Canada, 1981) and the two soft cheese outbreaks (California, 1985, andSwitzerland, 1983 (12). However, both MEE and ribotyping have relatively low discriminatory power.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the importance of L. monocytogenes epidemiology to human health, a number of discriminatory subtyping methods have been described for this organism (2,6,9,15,16,19,21,22,27,31). Although pulsed-field gel electrophoresis is the most commonly employed subtyping technique, new subtyping technologies are constantly introduced and tested in hopes of increasing the resolution, speed, and reproducibility of L. monocytogenes subtyping.…”
mentioning
confidence: 99%
“…Over the last decade, a vast number of reports of inexpensive and rapid methods to type Listeria spp. have been published 8,20,22,62,66) . The overall goal has been to develop methods that are more discriminatory than existing serotyping and phage-typing methods.…”
Section: Genetic Properties Of L Monocytogenesmentioning
confidence: 99%